Assessment of the diagnostic value of immunocytochemitsry and in situ hybridization in cytological specimen of childhood leprosy - Parvez, Mohd.; Dayal, R.; Natrajan, M.; Kamal, Raj (International Journal of Contemporary Pediatrics, 2018)
Background: Hardly any studies have been done to study diagnostic value of immunocytochemistry and in situ hybridization in cytological specimens for the diagnosis of leprosy in children. The objective of this study is to assess the diagnostic value of immunocytochemistry and in situ hybridization in cytological specimens of leprosy patients. To compare these techniques with Z.N. staining. Methods: This prospective study was carried out in 24 patients (≤18 years of age) of leprosy. Clinical examination of each patient was done and categorized according to IAL. After taking consent, three skin smears was taken, one for Z.N. staining and remaining two for immunocytochemistry and in situ hybridization respectively. Results: Routine skin smear examination by ZN staining method confirmed the diagnosis in 2/24 (8.3%) cases and they belonged to BL category. Immunocytochemistry showed positivity in 4/7 (57.1%) in early leprosy (BT) and 82.3% (BB/BL) in late leprosy. Immunocytochemistry improved the diagnosis by 66.7%, and the results were statistically significant (p<0.01). In situ hybridization showed the positive results in 66.6% cases of early leprosy and 86.6% cases of late leprosy (BB/BL). In situ hybridization improved the diagnosis 72.6% in comparison to ZN staining and the results were statistically significant (p<0.01). Conclusions: Immunocytochemistry and in situ hybridization enhance the diagnosis of leprosy when compared to routine skin smears stained by ZN staining. They are important diagnostic tools for definitive diagnosis in early as well as established cases of leprosy.